The Coping Self-Efficacy Scale: Psychometric properties in an outpatient sample of active duty military personnel. Issue 3 (3rd May 2020) - Cunningham, Craig A.; Cramer, Robert J.; Cacace, Sam; Franks, Michael; Desmarais, Sarah L.
ABSTRACT: Active duty military service members endure a unique constellation of stressors while deployed or at home. Yet, assessment of protective factors against these stressors among active duty service members represents an under studied area. The present study advances the assessment of protective factors through the psychometric evaluation of the Coping Self-Efficacy Scale (CSES) in a clinical sample of military service members in mental health or substance abuse treatment ( n = 200). Cross-sectional data were drawn from military medical records and a supplemental self-report questionnaire. Data extracted included demographic (e.g., sex, age), military characteristics (e.g., rank, years in service), physical health and mental health (e.g., anxiety, depression), and coping self-efficacy. Findings suggest a 3-factor (i.e., problem-focused coping, thought-stopping, and getting social support) CSES structure with acceptable internal consistency. Further, there were small-to-moderate associations with physical and mental health outcomes, providing evidence of construct validity. There were few significant associations with military-related characteristics. Finally, controlling for covariates, thought-stopping beliefs explained unique variance in suicide-related behaviors. Together, findings support the use of the CSES to measure coping-related beliefs in military service members. Recommendations are offered for future research and practice with active duty service members.